2020
DOI: 10.4103/jmu.jmu_26_19
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone levels and ultrasonographic changes in the thyroid gland of patients on long-term Lithium treatment for affective disorders: A controlled study

Abstract: Background: Although lithium is known to cause thyroid dysfunction and increased thyroid gland volume, clinical examination and biochemical assessment are fundamental to thyroid workup of patients on lithium treatment. We aimed to determine thyroid gland volume and the Thyroid hormone levels of patients who have been receiving lithium treatment for affective disorders in comparison to voluntary healthy controls. Methods: This was a cross-sectional, hospital-based observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Some studies suggest a higher risk in females, the elderly, and individuals with diabetes 13 . Small case-control studies conducted in India have suggested thyroid gland enlargement and higher average TSH levels in individuals undergoing Lithium treatment 14,15 . However, prospective studies with follow-up duration between 2-15 years provide inconclusive findings.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest a higher risk in females, the elderly, and individuals with diabetes 13 . Small case-control studies conducted in India have suggested thyroid gland enlargement and higher average TSH levels in individuals undergoing Lithium treatment 14,15 . However, prospective studies with follow-up duration between 2-15 years provide inconclusive findings.…”
Section: Introductionmentioning
confidence: 99%
“…Even though many investigations reported that low levels of Li + are precious in mitigating signs of bipolar disorders and depression ( 6 8 ) found that prolonged exposure to therapeutic doses of Li + triggers complications among hospitalized patients ( 8 ). Hence, toxicity in the renal system ( 9 11 ), nervous system ( 12 ), thyroid glands (goiter) ( 13 ), and dermatological-related complications ( 14 , 15 ), as well as circulatory system ( 16 ) under Li + exposure have been earlier reported. On the other hand, it has been shown that this light metal can pass across the placental barriers and then induce teratogenic effects ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%